HOW CORRUPTION ADAPTS TO E-PROCUREMENT : A STUDY IN NORTH SUMATRA - Hendro Siahaan; Widia Astuty (PT. Radja Intercontinental Publishing, 2026)
Improving the Goods/Services Procurement (PBJ) sector is one of the government's top priorities in order to improve development, public services, and prevent corruption. One manifestation of this is the establishment of the Government Goods/Services Procurement Policy Institute (LKPP) to implement the development and formulation of government PBJ policies. A number of innovations have been developed in the form of E-Procurement such as SPSE (Electronic Procurement System) and E-Catalog. However, the rampant corruption in PBJ amidst these improvements indicates that the improvements made have not been sufficient to mitigate the problem of corruption in PBJ. This phenomenon raises critical questions about the extent to which E-Procurement functions as an instrument for preventing corruption or actually creates new space for the adaptation of corrupt practices.